The relationship of service quality dimensions of restaurant enterprises with satisfaction, behavioural intention, eWOM, and the moderating effect of atmosphere - Uslu,Abdullah (2020)
Abstract The aim of this research is to test the relationship between the service quality of restaurants and electronic word-of-mouth (eWOM) communication, satisfaction, and behavioural intention and to analyse the moderating effect of the restaurant atmosphere in the relationship between service quality and eWOM. The population of the research consists of local tourists who come to the restaurants located in the city centre of Diyarbakır. Questionnaires were used to obtain the data of the research. The data were analysed using 385 surveys collected from restaurant customers using package programs (SPSS and AMOS). As a result of explanatory factor analysis, 4 service quality dimensions were determined in restaurants (tangibles, assurance, reliability, empathy), and then confirmatory factor analysis, second-order confirmatory factor analysis, a measurement model, and path analyses were carried out. According to the results of the analysis, it was determined that the service quality dimensions of the restaurants have effects on satisfaction and eWOM. In addition, restaurant atmosphere has been found to have a moderating effect on the effect of service quality dimensions on eWOM in restaurants.